Celebrity CEO, Identity Threat, and Impression Management: Impact of Celebrity Status on Corporate Social Responsibility - Lee,Gilsoo; Cho,Sam Yul; Arthurs,Jonathan; Lee,Eun Kyung (Journal of Business Research, 2020)
In this study, we examine the impact of CEO celebrity status on the propensity of firms to engage in corporate social responsibility (CSR). Integrating identity and impression management theories, we argue that a firm’s engagement in CSR activities is affected by a celebrity CEO’s impression management motive to maintain his/her identity and status as a celebrity. We then explore three boundary conditions under which the effects of celebrity status on CSR may be strengthened. We find that celebrity CEOs’ engagement in CSR activities as an impression management tactic increases when uncertainty surrounding a firm’s expected performance is high, when firm performance is low, and the competitive intensity of the industry is high. The findings of this study provide useful insights into the specific ways by which celebrity CEOs attempt to protect their established status and reputation. This paper contributes to various domains of research concerning CEOs, impression management, and CSR.
Keywords: Strategy & Entrepreneurship